1989
DOI: 10.1002/oms.1210240205
|View full text |Cite
|
Sign up to set email alerts
|

Secondary processes in mass spectrometry of alkylmercury halides

Abstract: The sensitivity of the mass spectrometer towards RHgX alkylmercury halides in the electron impact technique was found to decrease in the order X = Cl > Br > I. The intense peaks corresponding to the more heavy halides registered in the mass spectra of RHgX were shown to arise owing to the secondary processes of halogen exchange occurring in the mass spectrometer. The non‐volatile bromine and iodine compounds adsorbed in some form on metallic surfaces of the ionization chamber (so‐called ‘memory effect’) could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The agreement between GC-MS results and those obtained with a standard GC-electron-capture detection system and by neutron-activation was good-within 10% (35). Similarly, MeHgI conversion to MeHgCl occurred (34,161). As a result of these observations, the GC procedure was improved by the addition of MeHgCl to the samples or by repeated injections of microgram amounts of MeHg (162).…”
Section: Spectrometry Of Organomercury Compoundsmentioning
confidence: 97%
See 3 more Smart Citations
“…The agreement between GC-MS results and those obtained with a standard GC-electron-capture detection system and by neutron-activation was good-within 10% (35). Similarly, MeHgI conversion to MeHgCl occurred (34,161). As a result of these observations, the GC procedure was improved by the addition of MeHgCl to the samples or by repeated injections of microgram amounts of MeHg (162).…”
Section: Spectrometry Of Organomercury Compoundsmentioning
confidence: 97%
“…All attempts at fractionation have been unsuccessful, indicating that the bromides and iodides might not be impurities (34,35). The origin of these ions in the mass spectra of AlkHgCl has been investigated in detail under various experimental conditions (34). Some of the results indeed indicated that bromides and iodides were not present in the initial samples.…”
Section: Spectrometry Of Mercury Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…This fragmentation pathway gives the most abundant product-ion peaks (100% relative abundance) by collision-induced fragmentation of MH+ ions. The compounds 3 [1,1], 8[2,2] and 12[3,3] with equal-length polyoxyethylene chains (m = n) decompose according to Reaction (1) to form the product ions 147+, 191+ and 235+, respectively, which are known from the EI mass spectra of crown ethers to be [M/2+ 11' ions. In the CID MIKE spectra of the MH+ ions of the compounds, the more-abundant product ions are formed from the MH+ ions by loss of the smaller neutral molecule (x = n if n < m).The second decomposition route of MH+ ions, the elimination of molecules with masses of 59u, 103u, 147 u, 191 u and 235 u is pronounced.…”
mentioning
confidence: 99%